Determinan Kepatuhan Wajib Pajak Dalam Membayar Pajak Kendaraan Bermotor Pada Kantor Samsat Wilayah Kota Jayapura - Da Lopez, Erika Cornelia; Pangayouw, Bill J. C; Wonar, Klara (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2023)
This research aims to examine the influence of Tax Sanctions, Tax Knowledge, Taxpayer Awareness, Tax Socialization and Tax Whitening on Taxpayer Compliance in paying Motor Vehicle Tax. This research uses a descriptive quantitative approach. The population in this section is all motor vehicle taxpayers who have been recorded at the Jayapura City Regional Samsat Office, namely 221,665 according to the number of vehicles recorded. The sampling technique used Accidental Sampling and the number of samples in this study was 135 respondents who were registered motor vehicle taxpayers in the Jayapura City Area. Data collection techniques use observation and questionnaires with a Likert scale. The analytical tools used are quantitative descriptive analysis and Partial Least Square (PLS) with the help of the WarpPLS version 8.0 application. The research results show that: 1) Tax sanctions have no effect on taxpayer compliance in paying motor vehicle tax. 2) Tax knowledge has a positive and significant effect on taxpayer compliance in paying for motor vehicles. 3) Taxpayer awareness has no effect on Taxpayer Compliance in paying for Motor Vehicles. 4) Tax Socialization has no effect on Taxpayer Compliance in paying for Motor Vehicles. 5) Tax whitening has a positive and significant effect on taxpayer compliance in paying for motor vehicles.